2015
DOI: 10.1186/s40425-015-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

Baseline circulating IL-17 predicts toxicity while TGF-β1 and IL-10 are prognostic of relapse in ipilimumab neoadjuvant therapy of melanoma

Abstract: BackgroundWe evaluated candidate circulating serum cytokines, chemokines and growth factors in patients with locally/regionally advanced melanoma receiving neoadjuvant ipilimumab with toxicity and clinical outcome.MethodsPatients were treated with ipilimumab (10 mg/kg IV every 3 weeks, 2 doses) before and after surgery. xMAP multiplex serum testing for 36 functionally selected cytokines and chemokines was performed at baseline and at six weeks (following ipilimumab). Based on our prior data, the association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
252
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 334 publications
(260 citation statements)
references
References 32 publications
3
252
1
4
Order By: Relevance
“…Biomarker and mechanistic data nested within this study have supported the immunotherapeutic predictive value of the proinflammatory tumor microenvironment as measured by mRNA expression and CD8 T cell density at the tumor invasive margin [88]. Other studies have supported a role for the TH17 pathway in mediating immune related colitis after treatment with ipilimumab [89]. Ongoing studies are testing the neoadjuvant therapeutic value ipilimumab in combination with IFNα (NCT01608594), pembrolizumab in combination with IFNα (NCT02339324) and the combination of ipilimumab-nivolumab as compared to nivolumab alone (NCT02736123).…”
Section: News On Immunotherapysupporting
confidence: 55%
“…Biomarker and mechanistic data nested within this study have supported the immunotherapeutic predictive value of the proinflammatory tumor microenvironment as measured by mRNA expression and CD8 T cell density at the tumor invasive margin [88]. Other studies have supported a role for the TH17 pathway in mediating immune related colitis after treatment with ipilimumab [89]. Ongoing studies are testing the neoadjuvant therapeutic value ipilimumab in combination with IFNα (NCT01608594), pembrolizumab in combination with IFNα (NCT02339324) and the combination of ipilimumab-nivolumab as compared to nivolumab alone (NCT02736123).…”
Section: News On Immunotherapysupporting
confidence: 55%
“…In contrast, there was little association with Anti-Saccharomyces Cerevisiae Antibody, anti-CBir1 or anti-I2 antibodies 17. Higher baseline serum interleukin (IL)-17 levels have also been shown to correlate significantly with the incidence of grade 3 diarrhoea and colitis (p=0.02) 18. In addition, increasing eosinophil blood count during treatment with ipilimumab was associated with increasing rate of irAE 19.…”
Section: Resultsmentioning
confidence: 99%
“…In patients with advanced inoperable melanoma, a better understanding of the regulation of cytokine and cellular immune activity in response to melanoma may be important in order to predict therapeutic response to immunotherapy, including treatment with ipilimumab. A recent study showed that in patients with regionally advanced melanoma enrolled in a trial of neoadjuvant therapy with ipilimumab at 10 mg/kg, baseline IL‐17 level was significantly associated with the risk of subsequent development of severe immune‐mediated diarrhea/colitis . Further investigation and confirmation in larger trials is necessary in order to confirm these findings.…”
Section: Il‐17 and Oncological Skin Diseasesmentioning
confidence: 99%